WOMEN-WRITERS IN ENGLISH LITERATURE - Eshmamatov Artur Bekmamat oʻgʻli , (TADQIQOTLAR.UZ, 2024)
In this article, we will explore the influence of women writers on the development of English literature, highlighting key figures and their notable works. From the pioneering works of Mary Shelley to the powerful poetry of Sylvia Plath, Dame Agatha Christie, women writers have made enduring contributions that continue to resonate with readers worldwide.